Pitanje univerzalne odgovornosti i religijskog morala kao mogući faktori mira - Donev, Dejan (Centar za istraživanje religije, politike i društva, Novi Sad & Hrišćanski kulturni centar dr Radovan Bigović, Beograd, 2014)
Each our act have also personal and universal dimensions. Therefore the ethical discipline, and also for the religion, careful judgment and positive concrete behavior are conditions for a happy and fulfilling life. Nowadays, a case of one side of the world can have a direct or indirect consequences across the globe. Therefore we need a universal responsibility in which a big active part have the religious moral and responsibility, especially in efforts to establish a lasting peace, as our particular work activity, endeavor. An example of this through which the author attempts to illustrate the previous noted thesis are the religious gatherings in Assisi.
The question of universal responsibility and religious moral as a possible peace agent
Keywords: Responsibility, religious ethics, peace & reconciliation